Methodical instructions for practical lessonson the subject "Financial Controlling" - Druhova, О. S.; Klepikova, S. V.; Makarenko, Anastasiya B.; Yakovlev, V. I. (National technical university "Kharkov politechnical institute", 2021)
Improving the management system, enterprises focus on achieving the main mission –obtaining optimal profits, maximizing cost of the owners’ pitalwhile minimizing risk and maintaining liquidity and solvency, as well as solving specific operational, current and strategic objectives. In this sense, an important factor in such a system is financial controlling. Financial controlling is a fundamentally new concept in enterprise management, which is able to ensure the process of monitoring, analysis, planning and controlling over the movement of financial resources and cash flows in order to make optimal management decisions to maximize profits, minimize financial risks and ensure the well-being of owners, support of internal balance of the enterprise economy and its effective development by forming objective information on cost and incomes that allows making optimal administrative decisions. Financial controlling is focused on the functional support of financial management. According to the industry standard of higher education of the Ministry of Education and Science of Ukraine, the discipline "Financial Controlling" is an optional component of the cycle of professional and practical training in specialty 072 "Finance, Banking and Insurance". The discipline "Financial Controlling" has a logical and content methodological relationship with other disciplines of the educational and professional program. To master this discipline, students need prior knowledge and skills acquired during the study of the following disciplines: "Macroeconomics", "Microeconomics", "Mathematics for Economists", "Money and Credit", "Finance", "Financial Activity of Business Entities".
Keywords: methodical instructions; financial controlling; Finance, Banking and Insurance; financial diagnostics; budgeting; strategic